Assessment of Green Logistics Practices in Downstream Petroleum Industries for the Transition to Circular Economy - Ahmad Ghorbanpour; Abdolkarim Hosseinpoor (Environmental Energy and Economic Research)
Environmental damage such as global warming, climate change, reduction of natural resources, emission of greenhouse gases, etc. have caused the transition of production systems towards sustainable development and circular economy. One of the main drivers of these systems is green logistics, the implementation of which can reduce the destruction of the environment. green logistics is the main trend of the transition towards modern logistics and as a basic system of circular economy development. It links resources and products, products and consumers and is very useful for closing the circle of circular economy. The main purpose of this study is to identify green logistics practices and analyze their importance. In first, a number of the green logistics practices are extracted from related reviews of the studies. Data collection tool was a researcher-made questionnaire. The green logistics practices were validated using experts’ opinions in academic and industry. Then, the Best-Worst Method(BWM) was used to determine the importance of practices. In first, the mathematical model was programmed in Lingo 18.0 software. Then, based on the opinions of each expert, the weight of practices and the inconsistency rate were calculated. By averaging, the final weight of the practices was obtained. The inconsistency rate was calculated 0.035, which is acceptable. The findings show that green purchasing and end-of-life practices have weights of 0.213 and 0.189, respectively. it can be said that they are very important. Therefore, it is suggested to pay more attention to these two factors for the transition to circular economy.